Study of serum lipid profile in psoriaticpatients and correlation with disease severity - R. Abu-Raghif, Ahmed; M. Al.jubori, Osama; Khalaf Noaman, Shathel (Tikrit Journal of Pharmaceutical Sciences, 2023)
Introduction :Psoriasis is a chronic proliferative skin disorder with reported incidence of 1.5%-4.8% in different countries. Its etiology is still unknown, while genetic, metabolic and immunological mechanisms have been recommended as its causes. Literature suggests that lipid metabolism maybe play a significant a role in pathogenesis of psoriasis, and psoriatic patients manifest significant lipid abnormalities.Patients and Methods: The study comprised 53 psoriatic patients and 50 age and sex matched healthy subject. For all patients, clinical assessment by using Psoriasis Area and Severity Index (PASI) score was performed, and fasting blood sampling was collected to assess the lipid profile.Results: Psoriatic patients, in comparison to healthy subjects, show a significant high serum level of total cholesterol (TCH) and low-density lipoprotein cholesterol (LDL) and no significant differences in the serum level of triglyceride (TG), very low-density lipoprotein cholesterol (VLDL), and high-density lipoprotein cholesterol (HDL). Conclusions: Psoriatic patients were associated with lipid abnormalities. Atorvastatin shows a promise role in treatment of psoriasis. Furthermore, Atorvastatin demonstrate a beneficial therapeutic role in psoriasis by its hypolipemic efficacy. Further studies were recommended to assess the therapeutic efficacy of lipid lowering drugs in treatment of psoriasis